Perceived Gaze Direction Modulates Neural Processing of Prosocial Decision Making - Sun, Delin; Shao, Robin; Wang, Zhaoxin; Lee, Tatia M. C. (Frontiers in Human Neuroscience, 2018)
Gaze direction is a common social cue implying potential interpersonal interaction. However, little is known about the neural processing of social decision making influenced by perceived gaze direction. Here, we employed functional magnetic resonance imaging method to investigate 27 females when they were engaging in an economic exchange game task during which photos of direct or averted eye gaze were shown. We found that, when averted but not direct gaze was presented, prosocial versus selfish choices were associated with stronger activations in the right superior temporal gyrus (STG) as well as larger functional couplings between right STG and the posterior cingulate cortex (PCC). Moreover, stronger activations in right STG was associated with quicker actions for making prosocial choice accompanied with averted gaze. The findings suggest that, when the cue implying social contact is absent, the processing of understanding others’ intention and the relationship between self and others is more involved for making prosocial than selfish decisions. These findings could advance our understanding of the roles of subtle cues in influencing prosocial decision making, as well as shedding lights on deficient social cue processing and functioning among individuals with autism spectrum disorder.